Genetic variation of clonal Ananas comosus var. MD2 plants after mutagenic treatment at different post-recovery periods / Anis Norsyahira Mohd Raffi - Anis Norsyahira , Mohd Raffi (2020)
Studies on genetic variation in plants had become extensively employed in research for plant improvement and conservation. Due to their sessile nature, plants are exposed to various environmental stressors such as exposure to enhanced levels of ultraviolet (UV), ionizing and non-ionizing radiations. Exposure to these harmful radiations will result in various damages, ranging from DNA and chromosomal aberrations to phenotypic abnormalities. However, plants have evolved efficient DNA repair mechanisms to detect and repair any DNA damages caused by the exposure to these harmful stressors, therefore ensuring their survival. In this study, the effect of gamma radiation (as a source of ionizing radiation) on clonal Ananas comosus var. MD2 was evaluated. The morphology of the clonal plantlets before and after exposure to gamma radiation was monitored at timely intervals (at different post-recovery period). Moreover, the degree of genetic variation between the samples pre- and post-irradiation was also analyzed by using inter-simple sequence repeat (ISSR) markers. Data analysis revealed that the height of the irradiated plantlets were significantly reduced (compared to control), but improved with recovery period. These observations were also supported by the ISSR analysis, where the genetic dissimilarity between the irradiated samples and control was reduced by 0.1017, after 4 weeks of recovery. Eight of 20 tested ISSR primers provided a total of 4169 bands in 10 non-irradiated and irradiated plantlets (randomly collected). The number of scorable bands per primer varied from 8 to 13 which generated an overall of 303 polymorphic bands, with a mean of 30.3% polymorphism. Our findings indicated that the phenotype recovery undergone by the clonal A. comosus var. MD2 plants was contributed by their ability to detect and repair the DNA lesions (as exemplified by the reduction in genetic dissimilarity after 4 weeks) and hence allow the plantlets to undergo phenotype reversion to normal plant stature.